Progressive high-fluence epithelium-on accelerated corneal crosslinking: a novel corneal photodynamic therapy for early progressive keratoconus - Mazzotta, Cosimo; Pandolfi, Anna; Ferrise, Marco (Frontiers in Medicine, 2023)
Abstract Purpose: To assess the preliminary clinical results of a new progressively higher fluence pulsed light Epi-ON accelerated crosslinking nomogram (PFPL M Epi-On ACXL) in the treatment of progressive keratoconus (KC). Setting: Siena Crosslinking Center, Siena, Italy. Methods Prospective pilot open, non-randomized interventional study including 32 eyes of 32 young-adult patients over 26 years old with Stage I-III progressive KC undergoing PFPL M Epi-On ACXL. Riboflavin loading was performed by using Paracel I 0.25% for 4 min and Paracel II 0.22% for 6 min. The Avedro KXL System (Glaukos-Avedro, Burlington, USA) was used for pulsed-light Accelerated Crosslinking (ACXL) at air room 21% oxygenation and 13 minutes of UV-A irradiation. The treatment fluence was set at 7.2J/cm2, 8.6 J/cm2 and 10.0 J/cm2 in corneas with baseline pachymetry <420µm (group 1: 8 eyes), ≥ 420µm < 460µm (group 2, 11 eyes) and ≥ 460µm (group 3, 13 eyes) respectively. Uncorrected distance visual acuity (UDVA), Best spectacle corrected visual acuity (BSCVA) Scheimpflug corneal tomography and anterior segment OCT (AS-OCT) data were collected at baseline and postoperative 1, 3 and 6 months. Results UDVA and BSCVA improved in all groups (P≤0.05). Maximum keratometry values (K max) showed a significant decrease in the 10.0 J/cm2 group (Δ − 1.68 D). The coma (HOAs) value improved significantly by the sixth month in all groups. OCT average demarcation lines were 211±19 µm in group 1, 245±23µm in group 2 and 267±21µm in group 3 respectively. Conclusions: The preliminary results show that pachymetry-based PFPL M Epi-On ACXL nomogram stabilises ectasia progression. Higher fluence Epi-On ACXL increases CXL penetration with better functional outcomes in absence of complications.